PERAN PENYULUHAN TERHADAP PETANI KARET POLA SWADAYA DI KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU - Asrul Taufik; Rosnita '; Eri Sayamar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Rubber plantations are one of the source life for people of Riau . Most of the rubber plantations in Riau Province is dominated by smallholder plantations cultivated independently on a small scale and traditional. So that production tends not optimal. This is due to farmers' lack of knowledge of how to farm properly. The government's concern for farmers who are independent smallholder is expected through extension. The purpose of this research are to analyze the roles of what is already run by agricultural extension workers to independent rubber farmers in Peranap District views of education, dissemination, facilitation, consultation, supervision and monitoring / evaluation. This research was conducted in Semelinang  Darat and Pauh Ranap Village Peranap District Indragiri Hulu Regency. The method used is survey with a sample of 120 independent smallholder rubber farmers, with details of each village was taken 60 respondents. The results showed that the role of education is quite a role in the activities of rubber farming in the district Peranap, as seen from education, dissemination, facilitation, consultation, supervision, monitoring and evaluation with a score of 2.83. Extension instrumental in educating farmers indicated by a score of 2.94, dissemination of information with a score of 2.79, with a score of 2.67 facilitation, consultation with a score of 2.93, with a score of 2.79 supervision and monitoring and evaluation with a score of 2, 87. Keywords: The role of extension, Independent smallholder rubber farmers